Laboratory Studies on Stone Mastic Asphalt with varying fillers - Vijay B.G.; Madinur Niveditha; Sanganaikar Raghavendra S. (E3S Web of Conferences, 2023)
Stone Mastic Asphalt (SMA) is based on the concept of designing a coarse aggregate skeleton in order to attain stone -on -stone contact is obtained, which provides a highly rut resistant bituminous course for heavy traffic loads. It is a homogeneous mixture of selected gap graded aggregate, filler and bitumen in such proportion as to yield a plastic and void less mix. The main objective of this study is to evaluate the effect of different fillers (stone dust, bagasse ash and palm oil fuel ash) on the SMA mixes in terms of Marshall Stability values. A comprehensive laboratory tests were conducted on aggregates, Bitumen (VG-30) and fillers. The prepared SMA specimens with varying combination of filers such as 10% of stone dust, 5% of stone dust and 5% of Bagasse ash, 5% of stone dust and 5% of palm oil fuel as along with 0.3% of mineral additive (waste plastic) were subjected to marshall stability tests and results indicates that use of partial replacement of bagasse ash for stone dust as a filler material gives more stability values and less voids when compared to absolute stone dust (10%).